1992
DOI: 10.1108/01437739210022847
|View full text |Cite
|
Sign up to set email alerts
|

Self‐managing Work Teams: An International Perspective

Abstract: Documents the utilization of the self‐managing work teams concept throughout the world. Specifically, explores such utilization in Australia, Canada, Japan, Sweden, the United Kingdom and the United States of America. Also investigates the pioneering use of that concept by the unions, e.g. the Communication Workers of America. Demonstrates the value of this new concept in enhancing global competitiveness. Also looks at the impact of the dominant cultural paradigm and its possible effect on the success (or lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…The first phase involves the establishment and development of an effective intrapreneurial team. Initially, the team develops through the stages proposed by Tuckman (1965) and then advances through the process of becoming a self‐managed team in a form as presented in the literature (Ankarlo, 1993; Carr, 1991; Holpp, 1993; Manz et al , 1990; Manz and Sims, 1987; Salem, 1992; Salem et al , 1992). The further development of self‐managed teams is progressed through an approach that has a knowledge development and management system that utilises the PDSA cycle (Deming, 1986).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The first phase involves the establishment and development of an effective intrapreneurial team. Initially, the team develops through the stages proposed by Tuckman (1965) and then advances through the process of becoming a self‐managed team in a form as presented in the literature (Ankarlo, 1993; Carr, 1991; Holpp, 1993; Manz et al , 1990; Manz and Sims, 1987; Salem, 1992; Salem et al , 1992). The further development of self‐managed teams is progressed through an approach that has a knowledge development and management system that utilises the PDSA cycle (Deming, 1986).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…This PDM form flourishes in many countries, mostly western (e.g. Australia, Canada, Sweden, the UK, and the USA; Salem & Banner, 1992). Despite the dominant individualistic orientation, team members manage to reconcile personal ambition in order to achieve more responsibilities and higher job interest and independence (Cohen et al, 1996).…”
Section: Self-managing Teamsmentioning
confidence: 99%
“…The adoption of SMWTs has been limited in the United Kingdom, where the present study was carried out. Comparing the United Kingdom with other major nations over recent decades, Salem and Banner (1992) noted that "the evolution of worker participation in the UK could be classified as stagnant, at best." However, it has also been reported that due to increasing pressures for high-performance work design, their wider usage is now becoming very apparent (Grayson, 1990;Salem & Banner, 1992).…”
Section: Background Of Self-managing Teamsmentioning
confidence: 99%